HUBUNGAN HIGIENE SANITASI TERHADAP KUALITAS AIR MINUM PADA DEPOT AIR MINUM ISI ULANG DI KECAMATAN TAMPAN KOTA PEKANBARU TAHUN 2019 - Melana Sari; Ridwan Manda Putra; Agrina Agrina (Jurnal Ilmu Lingkungan, 2019)
More than 100 million Indonesians lack access to clean water and 150 million contaminated water sources. The difficulty of the availability of clean water is now one of the problem factors due to high population density, which causes a decrease in the quality of drinking water. Regulation of the Minister of Health of the Republic of Indonesia No. 43 of 2014 concerning hygiene sanitation of industrial water treatment must meet the criteria for place, equipment and handlers. The analysis used in this research is descriptive analysis. The samples in this study were 48 industrial water treatment with the sampling technique used survey sampling. From observations that have been made, 33.33% of depots have qualified test certificates. The results of this study indicate that there is no significant relationship between place variables on drinking water quality with sig = 0.283. There is a significant relationship between equipment variables on drinking water quality with sig = 0.006. There is a significant relationship between the handlers of drinking water quality with sig = 0.006. Simulant significant test results obtained by sanitation hygiene on drinking water quality sig = 0.002, this means that there is a significant relationship simulant sanitation sanitation (place variables, equipment and handlers) on the quality of drinking water in industrial water treatment at Tampan subdistrict.